(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The sustainable bond market emerges in 2007-2008 but significantly impacts capital markets after 2015. It can be argued that one of the reasons for its development is due to the issuances from supranational financial institutions, governments, and other public sector organizations. This article focuses on sovereign bonds issued for sustainable development, covering four main themes: green bonds, social bonds, sustainability bonds, and sustainability-linked bonds. Using methods of descriptive statistics, analysis of variance and correlation-regression analysis, the article examines the position of sovereign bonds in the sustainable bond market and the achieved outcomes in the environmental and social spheres in issuing countries. The application of the methodology reveals an increasing share of sovereign bonds in the sustainable debt segment, along with a statistically significant relationship between thematic sovereign bond issues and the overall volume of thematic debt. Positive changes in the indices measuring the sustainable development of the countries suggest a policy of increasing the relative share of government securities with a thematic focus in the overall government debt market.